Stages of artistic development of children from the age of four to twelve years old / Dahlia Mohd Shariff - Mohd Shariff, Dahlia (2005)
The importance of visual art had been given little emphasis especially as the child grows up through formal school and had become secondary to the success of logical subjects such as languages and mathematics. The child was born with multiple intelligences which includes visual capabilities. The brain consists left, logical and right, creative brain hemispheres. Both these need to be exercised for total well-being of the individual. Training the sensory of sight and coordination of psychomotor should begin from the formative stages as it requires cultivation, exposure, practice and preseverence. The practice of creative thinking and psychomotor coordination in visual art lessons result in character and skill development (such as confidence, creativity, appreciation, initiative, resourcefulness and communication). This research was to provide a local based information on the Malaysian children as so far the information available to art educators for children were based on Western art educators and their children. This research was to provide a guideline for any art educator as to the stages of development of the children. Hence, should an educator be faced with a Malaysian child, he or she would know what the child’s stage of development was in terms of the artistic abililties especially as this was very much related to the child’s cognitive development which in turn was dependent on the development of the brain’s neocortex. In order to study and obtain the progression of the children’s artistic development as the grew from four to twelve years old, this research studied the children in three educational institutions in Kampung Tunku, SS1, Petaling Jaya, Selangor. The quasi experimental method was employed to compare between the private art studio for children and the general school system of the Child Enrichment Centre (pre-school, four to six years old) and the Sekolah Kebangsaan Kampung Tungku (Standard 1 to Standard 6, seven to twelve years old). Art tests were employed, three of which were based from established art educators’ tests and one introduced in this research as a development from the established one.The observations were made on 260 children’s actual drawings based on their spontaneous and intuitive responses in four art tests. For further clarification on the outcomes, interviews with the teachers, parents and children were also carried out to understand opinions and other related factors. The outcomes of this research will contribute to the development of the visual art education in Malaysia in that there will be a record of the stages of artistic development of local children and provide a method as to how art educators, parents and child developers may keep record and assess the child’s development through artistic development. As art can be a means to understand growth and thinking ability, the artistic stages of development would be reflective of the child’s physical and cognitive abilities.